Des images qui dénoncent ? - Damien Darcis (EchoGéo)
In this article, I would like to question the political power of images in the urban space. To do this, I rely on the confrontation of two types of images displayed in Calais, a city now associated with the "migrant problem". On the one hand, I will study four interventions by street artist Banksy. On the other side, I will analyze images made by anonymous artists, in remote, less visible sites, on the walls, on the doors or on the windows of "squats" harboring migrants in particular. While Banksy's images convey a political message denouncing the situation of migrants, politicians in Calais have said they want to protect these paintings. Conversely, anonymous images, which do not convey any political message, are systematically erased or rendered inaccessible. Based on the work of Michel Foucault, Jacques Rancière and Étienne Balibar, I would like to show that this paradox is perhaps explained less by the celebrity of Banksy than by the relation of images to space: the Banksy maintain, even perpetuate the divisions of space and the relations between social groups constituting the established order, whereas anonymous images suspend them for a time to make heterotopic places exist.